2007
DOI: 10.1002/dmrr.780
|View full text |Cite
|
Sign up to set email alerts
|

Genistein and daidzein prevent diabetes onset by elevating insulin level and altering hepatic gluconeogenic and lipogenic enzyme activities in non‐obese diabetic (NOD) mice

Abstract: These results suggest that genistein and daidzein play important roles in regulation of glucose homeostasis in type 1 diabetic mice by down-regulating G6Pase, PEPCK, fatty acid beta-oxidation and CPT activities, while up-regulating malic enzyme and G6PD activities in liver with preservation of pancreatic beta-cells. The supplementation of genistein and daidzein are seemingly helpful for preventing IDDM onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
129
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(147 citation statements)
references
References 53 publications
16
129
0
2
Order By: Relevance
“…37) Choi et al reported that genistein and daidzein prevent diabetes in non-obese diabetic mice. 38) In this study, fasting blood glucose and HbA 1c were both decreased in the administration of isoflavone on the feeding period of day 42 and day 92. A lower level in the serum insulin was also observed in HFISO group, but no difference was found in OGTT.…”
Section: Discussionmentioning
confidence: 48%
“…37) Choi et al reported that genistein and daidzein prevent diabetes in non-obese diabetic mice. 38) In this study, fasting blood glucose and HbA 1c were both decreased in the administration of isoflavone on the feeding period of day 42 and day 92. A lower level in the serum insulin was also observed in HFISO group, but no difference was found in OGTT.…”
Section: Discussionmentioning
confidence: 48%
“…Such an inconsistency between G6PDH activity and fat accumulation has also been observed in other studies. 35 In conclusion, supplemental daidzein reduced the backfat thickness, carcass fat content, concentrations of glucose and lipid metabolites in serum, and pH 24 , but increased the ICDH activity, color, intramuscular fat content, and marbling score of longissimus muscle in finishing beef cattle. These results indicated that supplementation with daidzein in diets can reduce the subcutaneous fat content, promote the accumulation of intramuscular fat, and improve marbling and quality of beef meat.…”
mentioning
confidence: 83%
“…Soy isoflavones have beneficial effects in IDDM management: 5 the consumption of genistein or daidzein reduces the blood glucose level and improves insulinemia in type 1 diabetic rats. [6][7][8] To our knowledge, no study has investigated the effects of soy isoflavones on glycogen synthesis in the muscle of a type 1 diabetic animal model. A French company, Sojasun Technologies, has developed a powder extracted from the soybean called Fermented Soy Permeate (FSP).…”
mentioning
confidence: 99%
“…To our knowledge, the literature data showing positive effects of isoflavones on the blood glucose level [6][7][8] used supra-physiological doses (equivalent to 25 to 75 mg/kg body weight vs. 2 mg/kg) and treated the animals over a longer period (up to 8 weeks vs. 3 weeks). Our study aimed to determine the effects of FSP at physiological doses; thus, the administration of a lower soy isoflavones dose could explain the lack of improvement in the blood glucose level.…”
mentioning
confidence: 99%